Gating Training Model Using a Gating Drill Tool to Improve Gating Accuracy for Pamulang Woodball Club in South Tangerang City - Yulianingsih, Ika; Al Ghani, M.; Nugraheni, Wening (Jurnal Pendidikan Jasmani (JPJ), 2024)
The end of the woodball game is to put a wooden ball through a gate installed in the ground. Victory is obtained from the lowest shot or few strokes on each track or several tracks. Gating is one of the techniques in woodball that determines the end of the game. Success in gating strokes cannot be separated from the training process carried out. Training is carried out on PWbC woodball players by adjusting the distance and position of the ball, without any training aids. Beginner players find it difficult to practice basic swing gating. Gating shots that are not yet stable and not right on target. PWbC woodball players waste gating shots when playing 12 fairways and 24 fairways. The aim of this research is to provide a gating practice model using a drill gating tool. Media tools have a role in training the basics of a consistent swing. The research method used in this research is experimentation. Using a one group pretest-posttest design. Data collection was carried out by measuring gating precision on 25 PWbC club participants in South Tangerang city, carrying out the test using a gating accuracy test instrument. The results obtained were 4 (four) participants in the very good category. Gating ability in the good category numbered 10 (ten) participants, in the medium category there were 7 (seven) people, then there were only 3 (three) participants who had the poor category in gating ability.